Early assessment of post‐surgical outcomes with pre‐pectoral breast reconstruction: A literature review and meta‐analysis. Issue 6 (18th January 2018) - Chatterjee, Abhishek; Nahabedian, Maurice Y.; Gabriel, Allen; Macarios, David; Parekh, Mousam; Wang, Fang; Griffin, Leah; Sigalove, Steven
Abstract : Background: Pre‐pectoral breast reconstruction is an emerging surgical approach. This study provides an early assessment of outcomes with the technique. Methods: A comprehensive literature review was performed through searches of PubMed ® /MEDLINE ® to identify studies on pre‐pectoral reconstruction. Patient characteristics and outcomes were extracted from studies and pooled. Linear relationships between complication rates and patient characteristics with pre‐pectoral reconstruction were analyzed. A meta‐analysis compared complication rates between pre‐pectoral and dual‐plane reconstruction. Results: Fourteen studies (406 women/654 breasts) were included. The most common complications with pre‐pectoral reconstruction were flap necrosis (7.8%), seroma (6.7%), capsular contracture (5.8%), and explantation (4.6%). No hyperanimation was reported. Significant correlation between previous radiation and flap necrosis, post‐operative chemotherapy and infection, hypertension and flap necrosis, diabetes and dehiscence, and smoking and explantation were found. A meta‐analysis of four studies comparing pre‐pectoral (135 women/219 breasts) and dual‐plane (230/408) reconstruction found no significant difference for likelihood of infection (odds ratio, 0.46; 95% confidence interval, 0.16‐1.30), explantation (0.83; 0.29‐2.38), necrosis (1.61; 0.77‐3.36), seroma (1.88; 0.71‐5.02), dehiscence (1.84; 0.68‐4.95), or capsular contracture (0.14; 0.02‐1.14). Conclusions: Complication rates are comparable following pre‐pectoral and dual‐plane reconstruction, indicating the pre‐pectoral technique may be a feasible option for appropriate patients.